Rural Sociology (Lexington Allen Press, Inc., 1983)
This paper looks at the characteristics of kingship arrangements in the palouse area of eastern Washington and northern Idaho and whether relative who farm together differ in innovativeness from those who do not farm with the relatives.
Keywords: Sociology